Threshold learning outcomes: a framework for incorporating professional accreditation and AQF standards into assessment blueprinting/mapping in healthcare disciplines. - O'Keefe, Maree; Henderson, Amanda; Jolly, Brian; McAllister, Lindy; Remedios, Louisa; Chick, Rebecca (Office for Learning and Teaching, 2014)
The outcomes of the ALTC Learning and Teaching Academic Standards project have reinforced the importance of ensuring ongoing alignment between threshold learning outcomes and professional accreditation standards. This is a framework developed through a harmonising project which worked across, and with, higher education institutions and healthcare professional accreditation agencies to identify and match the goals and expectations of educational, professional and governmental institutions in relation to quality assurance activities. Within a framework that is organised around the threshold learning outcomes, information was captured about teaching and learning practices, designs and environments, and assessment approaches that underpin contemporary healthcare professional education. The project specifically focused on a subset of health professions including medicine, dentistry, nursing and physiotherapy as demonstration disciplines. A detailed analysis within each of these demonstration disciplines directly informs development of the framework that can subsequently be more widely adopted.